Can elastography visualize kidney damage in bodybuilders with high protein intake? - Kantarcı, Umut; Punduk, Zekine; Senarslan, Omer (Progress in Nutrition, 2022)
Introduction: High muscle mass and protein consumption may lead to a rise in serum creatinine levels. Therefore, increased serum creatinine levels do not always imply kidney dysfunction. Elastography was proposed for detection of renal impairment. We investigated the correlation between kidney stiffness and kidney damage in bodybuilders who are on high-protein diet. Materials and Methods: Bodybuilders who were on high-protein diet were compared with control subjects. Blood urea nitrogen/creatinine ratios and estimated glomerular filtration rates (eGFR) were calculated. Bodybuilders were divided into two subgroups as per eGFR levels (Group A and B for eGFR below or above 90; respectively). Length, width, volume, cortical thickness, and echogenicity of both kidneys were analyzed by ultrasound. Elastographic Shear Wave Velocity (SWV) measurements were performed, and mean SWV values (m/s) were calculated for each kidney. Comparison of mean SWV values was performed between the groups and subgroups. Results: Nineteen bodybuilders and 20 healthy control subjects were included. Mean BUN and serum Cr levels were higher in bodybuilders than control subjects (p<0,05). Cortical thicknesses and echogenicity were both higher in bodybuilders (p<0,05). The SWV values were higher in bodybuilders than control group indicating increased stiffness (p<0,05). Among bodybuilders, SWV values were significantly higher in group A than in group B (p<0,001). Conclusions: Elastography can be utilized for detection and follow-up of alterations in kidneys of bodybuilders or patients consuming high protein diets. High SWV can be considered as an indicator of renal damage, while the levels of conventional biomarkers may give confusing results.